ENT600: Mini Fly Trap (MFT) / Muhammad Afiq Brohan, Nor Hanani Arifin and Muhammad Zahiruddin Md Din. - Brohan, Muhammad Afiq; Arifin, Nor Hanani; Md Din, Muhammad Zahiruddin (2018)
Mini Fly Trap (MFT) is a device intended to help the food handlers in their daily job for controlling the population of flies. It is known that safety and health issues is concern among people who are eating outside as we known that disease easily spread by insects such as flies, thus this device was developed. The conventional method is very risky to get the vector food borne disease from cross contamination of flies due to hygienic factor. This device uses lithium battery as main power source despite it also rechargeable. Mini Fly Trap also has solar panel on top of the device to generate power from solar energy as a supplementary power. This device is made of combination of stainless steel and high quality plastics. This Mini Fly Trap is lightweight and easily to bring and use by food handlers. Before the product is out in the market, public opinion by health workers from selected District Health Office is taken into account for acceptance and their opinions on improvements. This product and its process development were discussed further in the following chapters.